Effectiveness of Coping Training Programme in Enhancing Psychosocial Adjustment for Persons Living with HIV/AIDs in Nakuru North District, Kenya - Kariuki, Reuben G.; Muola, James Matee; Sindabi, Agrey M. (My University, 2012)
This was an experimental study which assessed the effectiveness of a coping training programme in enhancing psychosocial adjustment among persons living with HIV/AIDS (PLWHA) in Nakuru North Distrct, Kenya. A sample of 60 PLWHA assigned into an experimental (N=30) and control groups (N=30) participated in the study. Coping training was administered to the experimental group. Findings showed that training in coping enhanced psychosocial adjustment among the PLWHA.Though no statistically significant differences were found between the two groups in coping with HIV/AIDS, self-esteem and depression, the experimental group showed some improvement in these variables. A statistically significant (r = 0.368; P < 0.05) relationship between coping training and psychosocial adjustment was reported. Participants found the programme to be beneficial to them and they evaluated it positively.